PENERAPAN METODE BERMAIN PERAN UNTUK MENINGKATKAN KEMAMPUAN THEORY OF MIND PADA ANAK USIA PRASEKOLAH - Anindya Purnama (FKIP Unirow Tuban, 2016)
This study aims to determine the application methods play a role to improve Theory of Mind (TOM) to preschoolers. The study involved subjects were 32 children in kindergarten Bina Anak Sholeh (BAS) Tuban by dividing into two groups: the experimental group and the control group. The age range of children involved in the study ranging from 49-62 months of age. The average age of children was 54.9 months with comparison subjects by sex is a tad as many as 17 people (53%) while girls of 15 people (47%). Methods of data collection theory of mind to use the test consisted of 10 item question and measurement refers to the theories Wellman and Liu are the aspects of false belief includes the diverse desires, diverse belief, knowledge access, contents false belief, explicit false belief, belief emotion, and real-apparent emotion. Before the test the validity of data analysis based on professional judgment and item discrimination power of test results, while Test reliabilias using Cronbach's alpha with SPSS 22:00. The results showed that there was an increase in the ability of theory of mind in children of preschool age through methods play a role. This is indicated by an increase in theory of mind abilities score of 77% with the strong category.